2009
DOI: 10.1111/j.1399-6576.2009.01914.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of recovery after day surgery using a modified version of quality of recovery‐40

Abstract: A RECENT nationwide survey in Sweden found that day surgery accounts for 43% of all inhospital procedures. 1 Orthopaedic, general, and gynaecological procedures were the most common. About 40% of the day surgery units followed up with telephone calls within 1-2 days, and found pain to be the most common complaint. Quality of recovery had not been systematically evaluated with instruments tested for validity and reliability, and follow-ups beyond 2 days post-operative were not found.Quality of Recovery-40 (QoR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 15 publications
2
38
0
5
Order By: Relevance
“…(14) The QoR-40 responsiveness in other cultures was investigated between measures of pre-and postoperative periods, obtaining similar results -a moderate to significant effect. (15)(16)(17)(18) When investigating long term responsiveness, measurement between pre-and postoperative (90 days) of patients submitted to neurological surgeries, Australian researchers identified the QoR-40 good ability in detecting recovery changes (SRM>0.80). (19) The recovery monitoring over time showed that in the second return (about seven months after surgery), the QoR-40 scores were higher than the ones found in the preoperative period, characterizing an improvement in health status identified by the instrument.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(14) The QoR-40 responsiveness in other cultures was investigated between measures of pre-and postoperative periods, obtaining similar results -a moderate to significant effect. (15)(16)(17)(18) When investigating long term responsiveness, measurement between pre-and postoperative (90 days) of patients submitted to neurological surgeries, Australian researchers identified the QoR-40 good ability in detecting recovery changes (SRM>0.80). (19) The recovery monitoring over time showed that in the second return (about seven months after surgery), the QoR-40 scores were higher than the ones found in the preoperative period, characterizing an improvement in health status identified by the instrument.…”
Section: Discussionmentioning
confidence: 99%
“…The excluded items were from the dimensions physical comfort and pain, which did not present variability. (15) The same exclusion was identified in a study that developed a short version of the QoR-40. (19) This suggests that these items may not be essential to evaluate patients submitted to less invasive surgeries, as it was the case of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minor nature of breast surgery, low postoperative pain level, and sensitivity of the nine-item QoR may have contributed to it. The modified QoR-40 [28] for day surgery adopted in Abdallah et al's recent study [12] might be more sensitive for breast surgery as they have demonstrated the difference. However, since ours were inpatients due to the institutional policy, the recovery questionnaires for the ambulatory setting [28][29][30] were not considered for our study.…”
Section: Discussionmentioning
confidence: 99%
“…The modified QoR-40 [28] for day surgery adopted in Abdallah et al's recent study [12] might be more sensitive for breast surgery as they have demonstrated the difference. However, since ours were inpatients due to the institutional policy, the recovery questionnaires for the ambulatory setting [28][29][30] were not considered for our study. QoR-40 [14] and nine-item QoR [22] was designed for both inpatient-and outpatient-surgeries.…”
Section: Discussionmentioning
confidence: 99%